Vulnerability assessment method and its application in oil and gas pipeline industry - YAN Bingchuan; FENG Qingshan; ZHANG Hong; YANG Yue; ZHANG Han; SUN Chao; CHEN Jian; LIU Xiaoben (You-qi chuyun, 2023)
The vulnerability assessment method is mainly used to explore the security process of a system, with wide application in the fields of hazard management, ecology and engineering. It has been gradually concerned by the oil and gas pipeline industry in recent years. Therefore, a comprehensive survey was conducted for the concepts of vulnerability, the concept development and evolution process of vulnerability was clarified,and the main connotations of vulnerability applied in different fields presently were summarized. The qualitative and quantitative vulnerability assessment methods at domestic and abroad were compared, with their advantages, disadvantages, applicable scope and key issues analyzed.Meanwhile, the application of vulnerability assessment methods in the oil and gas pipeline industry was sorted out in detail from the 3 aspects of vulnerability connotation, assessment index system and assessment method. The results indicate that the vulnerability assessment method varies with the research object and the disciplinary perspective in terms of the concept definition, the actual connotation and the assessment method. In the oil and gas pipeline industry, the vulnerability assessment method is still in the preliminary stage, and it is urgent to establish a unified vulnerability concept and assessment system for the oil and gas pipeline system. Compared with foreign research, the development of pipeline vulnerability research in China is relatively lagging, the assessment methods are mainly qualitative or semi-quantitative, and no scientific standard is available for the classification of index grades and the determination of index scores. Therefore, it is necessary to focus on the establishment and improvement of quantitative assessment models in the future.